Lama Penyinaran dan Daya Lampu LED Terhadap Pertumbuhan dan Hasil Microgreens Tanaman Bunga Matahari (Helianthus annus) - Nadia Tria Sendari; Rizka Novi Sesanti; Erie Maulana; Raida Kartina; Wika Anrya Darma; Dila Febria (Politeknik Negeri Lampung, 2023)
Microgreen Cultivation of sunflower is part of indoor farming that is currently being developed. Cultivating in indoor farming requare LED lights as a light source to replace sunlight. This study aims to obtain the best LED lamp power and irradiation time for the growth and yield of sunflower microgreens. This research was conducted in Natar from December 2021 until February 2022. Experimental design was used Split Plot Design (RAL) with two-treatment which was repeated 3 times. The main plot is the time of irradiation (6, 10, and 14 hours). The subplots are lamp power (8, 10, and 12 watts). Observation parameter included germination, plant height, width and number of leaves, root length, chlorophyll of leaf, fresh weight, dry weight. Data were analyzed by ANOVA and continued with the 5% BNT test. The results of this study showed that treatment of irradiation time was not significantly different in all observation parameters. And treatment of lamp powers was not significantly different in all observed parameters except plant height and chlorophyll of leaf. The treatment of 8 watt and 10 watt LED lamp power give the best results on plant height observation, which was 11.71 cm and chlorophyll of leaf which was 29.18 units. There no was interaction between irradiation time and LED light power on all observation parameters.